Chemometric optimization of solid-liquid extraction with low-temperature partition (SLE-LTP) for determination of persistent organic pollutants in Caiman yacare eggs - Sousa, Demetrio A. [UNESP]; Goncalves, Renato M. [UNESP]; Heleno, Fernanda F.; Queiroz, Maria Eliana L. R. de; Marchi, Mary Rosa Rodrigues de [UNESP] (Elsevier B.V., 2014)
This paper presents the optimization of a method based on solid-liquid extraction followed by low-temperature partition (SLE-LTP) for the determination of persistent organic pollutants (organochlorinated pesticides and PCBs) in the eggs of the Pantanal caiman (Caiman yacare). The chemometric approach included a 2(4) factorial design and a triplicate central point. The extractor solvent volume (8-10 mL), vortexing time (1-5 min), centrifugation time (5-15 min) and freezing time (4-12 h) were the variables considered and were tested at three levels, including triplicate tests at the central point. The evaluated response was the average recovery for all the analytes. The data showed the extractor volume and the vortex time to be the main factors that affect recovery. The optimized method includes 12 mL of extractor solvent, 5 min of vortexing time, 5 min of centrifugation time and 12 h of freezing time. Under these conditions the average recovery was 61% with a precision expressed as relative standard deviation (RSD) of 15% for sample with 22.5 ng g(-1) of sample. A GC-ECD was used for the determination of POPs. The experimental design was an important statistical tool for defining the experimental parameters in the use of this method for the extraction of organochlorine pesticides and PCBs. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Factorial designs; Multivariate analysis; Solid-liquid extraction; Low-temperature part